(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Observe the current status of knowledge and practice of urinary catheter care nurses at some surgical departments of Thai Binh Provincial General Hospital in 2022. Methods: A cross-sectional descriptive study was carried out on 122 nurses at 5 Departments of Surgery of Thai Binh General Hospital in 2022, based on 2 questionnaires: “Knowledge survey on associated urinary tract infections related to nursing catheter care” and “Clinical Practice Checklist for Catheter Care”. Results: 67,2% of nurses had knowledge at the expected level. The average score in knowledge of 6 areas was 22.1 ± 3.7. 72,0% of nurses achieved at the expected level in the practice of urinary catheter care; The overall average score was 22.5 ± 3.2. There was a significant relationship between professional qualifications and knowledge and practice of urinary catheter care; Care knowledge with urinary catheter care practice. Conclusion: More than 67% of nurses knew and practiced taking care of urine catheters at the expected level.